Ecobody technology: rapid monoclonal antibody screening method from single B cells using cell-free protein synthesis for antigen-binding fragment formation. Issue 1 (December 2017) - Ojima-Kato, Teruyo; Nagai, Satomi; Nakano, Hideo
Abstract We report a rapid and cost-effective monoclonal antibody screening method from single animal B cells using reverse transcription (RT)-PCR andEscherichia coli cell-free protein synthesis (CFPS), which allows evaluation of antibodies within 2 working days. This process is named "Ecobody technology". The method includes strategies to isolate B cells that specifically bind an antigen from the peripheral blood of immunised animals, and single-cell RT-PCR to generate DNA fragments of the VH and VL genes, followed by CFPS for production of fragments of antigen binding (Fab). In the CFPS step, we employed our techniques: 1) 'Zipbody' as a method for producing Fab, in which the association of heavy and light chains is facilitated by adhesive leucine zipper peptides fused at the C-termini of the Fab; and 2) an N-terminal SKIK peptide tag that can increase protein expression levels. Using Ecobody technology, we obtained highly-specific monoclonal antibodies for the antigensVibrio parahaemolyticus andE .coli O26. The anti-V .parahaemolyticus Zipbody mAb was further produced inE .coli strain SHuffle T7 Express in inclusion bodies and refolded by a conventional method, resulting in significant antigen-binding activity (K D  = 469 pM) and productivity of 8.5 mg purified antibody/L-culture.